Influence of service quality, loyalty programme and perceived value on word-of-mouth behavior of domestic and international airline passengers in India - Joemon Pappachan (Vilakshan (XIMB Journal of Management))
Purpose – This paper aims to investigate the combined effect of airline service quality (ASQ), loyalty programme and perceived value (PV) on word-of-mouth (WOM) behavior of passengers’ traveling to domestic and international destinations from India. Design/methodology/approach – Passenger’s perception on service quality, loyalty programme and PV varies with flight type, which can affect WOM. This study was designed to know whether destination based difference in passengers’ perception on airline services affects their WOM. Hence, a sample of 554 frequent passengers was taken, which includes 358 domestic and 196 international passengers. The responses were collected using well-structured questionnaire. The hypothetical model was developed and tested using structural equation modeling using analysis of a moment structures (AMOS). Findings – Travel destination (flight) type moderates significantly the effect of ASQ on WOM behavior. ASQ affects WOM behavior more in domestic passengers. PV and loyalty programme do not moderate significantly with respect to destination type. PV was found to have significant influence on international passengers. However, loyalty programme was significant among domestic passengers. Practical implications – Airline managers can develop appropriate marketing strategies targeting the passenger influencing attributes. ASQ is the most significant attribute applicable to both flight types. The airlines can focus on attractive ticket fares for international passengers and more loyalty programme benefits for domestic passengers. Originality/value – This study examined the combined effect of ASQ, loyalty programme and PV on WOM behavior of passengers traveling in domestic and international sectors, which has not been researched yet.